Requirement model of mobile supply chain for petrol transportation in Malaysia - Mohd Sharif, Kamal Imran; Mohamed Udin, Zulkifli; Ibrahim, Jafni Azhan; Omar, Mazni (2012)
The demand of mobile technology in Malaysia has been more than expected and continues to expand greatly. Mobile supply chain management is one of the systems that provide managing petrol transportation efficiently. The application of mobile technology, allow the information of petrol transportation to retrieve ubiquitously and ordering process can be done immediately. It will help the sales executive from the oil and gas company to closely monitor and ensure good delivery of petrol to customers. Thus, this study aims to design a requirement model for mobile supply chain management system for petrol transportation in one of the oil and gas company in Malaysia.The model will provide a better guideline for the mobile system developer to design and develop the system accordingly.There are three main phases involved in the study which are defining, analyzing, and validating requirements.Nevertheless the study only focused on capturing the functional requirements using Unified Modeling Language (UML) and concluded the constraints arose during the course of producing the model.